'n Model vir fasette van strategiese beplanning vir inligtingstelsels in organisasies - P. J.S. Bruwer (South African Journal of Business Management, 1990)
– The key to success for the information-system function in an organisation is an efficient planning system. According to Head (1967, 23) managers are classified in levels of strategic planning, management control and operational control. Managers on these levels are respectively responsible for long, medium and short term planning. The information-system function is compatable with other organizational functions. Like other organizational functions it also consists of managerial levels which has to plan for the effective and efficient utilization of scarce resources. In this research project data has been collected from top and middle managers of two large financial institutions in South Africa. Models were developed to assist management in their task of strategic long and medium term planning of the information-system function.
Keywords: 650